Increasing the reliability of reinforced concrete frames of multistorey buildings - A. P. Malyshkin; A. V. Esipov; M. A. Esipov (Архитектура, строительство, транспорт)
The aim of the numerical research was to develop a method to improve the reliability of multistorey buildings with monolithic reinforced concrete frames. The method was based on the analysis of the total area of possible slab destruction due to emergencies and failure of individual building elements located in different places in the plan and in height. To analyze the reliability of spatial reinforced concrete frames according to the principle of single failure of a separate load-bearing structure, we introduced the concept of failure area coefficient. It allowed us to estimate the failure effect of a load-bearing key element of the building on the total failure area of the building slabs. In spatial frame structures of multistorey buildings with reinforced concrete frame, the key elements of the structural system are columns, pylons, collars, beams and other elements that ensure the overall stability of the building. Increasing the overall reliability of the frame building suggest the introducing an additional reliability coefficient of survivability depending on the failure area factor. In addition, we proposed an algorithm for analyzing and rejection of unsuccessful structural systems of monolithic reinforced concrete frame buildings based on the evaluation of excessively high ratios of building failure area. We analyzed the structural systems on the example of two constructed multistorey residential and public buildings with monolithic reinforced concrete frames.